Effects of Anchovy By-Product-Based Diets Supplemented with Soy Lecithin on the Reproductive Performance of Red Claw Crayfish (Cherax quadricarinatus) - Majiun, Meccarren; Shapawi , Rossita; Yong, Annita Seok Kian; Tuzan, Audrey Daning; Lim, Leong Seng; Aznan, Alia Syafiqah (Jurnal Medik Veteriner, 2025)
The present study aimed to determine the growth and reproductive performances of red claw crayfish (Cherax quadricarinatus) fed formulated diets based on anchovy by-product meal, supplemented with varying levels of lecithin. The SL0 diet, containing 0% soy lecithin, was used as the control, and four experimental feeds were included with different lecithin levels: SL1: 1% soy lecithin, SL2: 2% soy lecithin, SL3: 3% soy lecithin and SL4: 4% soy lecithin. Five broodstock (four females and one male) were stocked in the square fiberglass tank (105 cm ´ 105 cm ´ 36 cm; 400L) and fed twice daily (0900h and 1600h) until satiation for 11 weeks. The data were analyzed using one-way ANOVA followed by Tukey’s test at p < 0.05. Growth and survival rates showed no significant differences among treatments. Notably, SL4 exhibited the highest gonadosomatic index (GSI) at 2.50 ± 1.99%, while SL3 had the highest hepatosomatic index (HSI) at 6.20 ± 1.18%. The spawning rate peaked in SL1 (63.89%), followed by SL0 (47.22%), SL2 (41.67%), SL3 (41.67%), and SL4 (25.00%). SL4 also had the highest fecundity (14.94 eggs/g female), with SL3 (10.72 eggs/g female) and SL0 (9.50 eggs/g female) following. Lipid content in muscle varied from 1.14% (SL4) to 1.46% (SL3), with no significant differences. However, lecithin inclusion notably affected lipid content in hepatopancreas and gonad, with SL1 exhibiting the highest hepatopancreas lipid (61.04%) and SL2 the highest gonad lipid (27.78%). The data suggest that dietary lecithin plays an important role in the reproductive performance of red claw crayfish. Overall, anchovy by-product meal has high potential to serve as a dietary ingredient in the feed formulation for both juvenile and broodstock of red claw crayfish.